PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN POWERPOINT UNTUK PEMBELAJARAN DIFERENSIASI PADA MATERI PERKEMBANGBIAKAN TUMBUHAN KELAS IV DI SDN 18 TOBOALI - Sherlie Trimurtias; Erika Fitri Wardani; Silvio Juliana Nabela (Universitas Muhammadiyah Bangka Belitung, 2025)
The challenge in implementing the Independent Curriculum is differentiated instruction, where teachers find it difficult to adapt media to students' learning styles (visual, auditory, and kinesthetic). This research analyzes and develops PowerPoint-assisted learning media to support students' learning styles in the plant reproduction material for Grade IV at SDN 18 Toboali. The applied method is the Research and Development ADDIE model. The research subjects consisted of 4 students from Grade IV-A and 26 students from Grade IV-B. Data were collected through student and teacher response questionnaires, validation by media and material experts, and test instruments. Validity was tested by media and material experts, while practicality and effectiveness were measured through micro and macro-scale experiments. Data processing was carried out using quantitative descriptive and qualitative descriptive analysis. The research findings indicate that the developed media obtained a feasibility score of 96% from media experts (very feasible) and 84% from material experts (feasible). The practicality of the media based on micro and macro-scale experiments separately reached 97.8% and 92.7% (very practical). Teacher responses were also positive. The effectiveness test results with a paired sample t-test showed significant results, with an N-Gain of 79%, indicating that this PowerPoint-assisted learning media is effective for differentiated instruction in science material.